Clinical, virological and phylogenetic characterization of a multiresistant HIV-1 strain outbreak in naive patients in southern Spain - González-Doménech, Carmen María; Viciana-Ramos, María Isabel; Palacios-Muñoz, María Rosario; Delgado, Marcial; Del Arco, Alfonso; Tellez, Francisco; Jarilla, Francisco; Fernández, Sonsoles; Clavijo-Frutos, Encarnación; Santos-González, Jesús Leandro (Oxford Academic, 2016)
Background: We describe the characteristics of an HIV-1 strain with six viral reverse transcriptase mutations (D67N, T69N/D, V118I, V179D, T215S and K219Q), which we have called the Malaga strain. This strain was detected in treatment-naive patients from southern Spain. Methods: The study was undertaken at the Virgen de la Victoria Hospital, Malaga, a reference centre for the study of HIV-1 genotype resistance in Andalusia (the 'Costa del Sol'), Spain. Genotypic resistance testing was done in an automated sequencer. Phylogenetic analysis was performed using a 630 bp region of the reverse transcriptase with the mutations mentioned. Results: Between 2007 and 2014, we detected the Malaga strain in 30 treatment-naive patients. All were MSM, seen at five hospitals on the Costa del Sol. In all cases, the HIV-1 was subtype B with viral tropism R5. Phylogenetic analysis based on the reverse transcriptase sequence showed consistent grouping (with a bootstrap value of the common node of 100%) of the isolates that shared the mutation pattern mentioned. This strain has not been detected elsewhere or in previously treated patients. All of the patients treated with first-line combination ART responded. Conclusions: We report a cluster of an HIV-1 strain with multiple resistance mutations that was transmitted over a period of >8 years, affecting 30 naive patients from the same geographical area. The strain was susceptible to first-line combination ART.
Keywords: Virus del SIDA; HIV; Multiresistant; Phylogeny; Outbreak; Naive